The Impact of Information Technology Methods on Accounting Information Quality: Empirical Evidence From Iran - Amir Najafi; Sedigeh Soleimanpur; Zoheir Morady (Journal of Information and Organizational Sciences, 2022)
Information Technology is a key factor in eliminating the limitations posed by time and location and gives a much better and a faster access to informaition. In other words, technology has revolutionized work methods as a result of which, the paper which was used as a substrate for writing the work upon it has now been replaced by an electronic substrate. The changes created by technology include the use of Blockchain, IoT (Internet of Things), Cloud Accounting and Big Data to do accounting in automated form.The statistical sample of this study is given on the basis of the 171 person Cochran formulae consisting of financial managers, accountants and auditors of the Tehran city. Empirical results show that the use of Information Technology has a very significant role on the quality of Accounting Information and all these factors are influential in the quality of accounting system.